2010
DOI: 10.1007/s10722-010-9598-9
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial genome diversity in Beta vulgaris L. ssp. vulgaris (Leaf and Garden Beet Groups) and its implications concerning the dissemination of the crop

Abstract: Four mitochondrial minisatellites were used to study cytoplasmic diversity in leaf and garden beet germplasm resources. Eleven multi-locus haplotypes were identified, of which one (named mitochondrial minisatellite haplotype 4, hereafter min04) was associated with male-sterile Owen cytoplasm and two others (min09 and min18), with a normal fertile cytoplasm. European leaf beet germplasm exhibited the greatest haplotype diversity, with min09 and min18 predominating. In North African leaf beet accessions, only th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…Skuza et al 2010, Ni et al 2011. We ⎯⎯⎯⎯ recently investigated cytoplasmic genetic diversity in leaf and garden beets and their wild relatives using mitochondrial minisatellites (Nishizawa et al 2007, Cheng et al 2011. The same minisatellites were used to characterize cytoplasmic diversity in Chinese sugar beet breeding lines (Cheng et al 2009).…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%
See 2 more Smart Citations
“…Skuza et al 2010, Ni et al 2011. We ⎯⎯⎯⎯ recently investigated cytoplasmic genetic diversity in leaf and garden beets and their wild relatives using mitochondrial minisatellites (Nishizawa et al 2007, Cheng et al 2011. The same minisatellites were used to characterize cytoplasmic diversity in Chinese sugar beet breeding lines (Cheng et al 2009).…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%
“…We previously used 4 mitochondrial minisatellite loci (TR1, TR2, TR3, and TR4; Nishizawa et al 2007) to analyze 748 individual plants from the leaf and garden beet groups or their close relatives. Among these we were able to distinguish 21 haplotypes, named min01 to min21 (Nishizawa et al 2007, Cheng et al 2011.…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%
See 1 more Smart Citation
“…Landraces proved to be distinct from modern garden beet cultivars. Cheng et al (2010) investigated cytoplasmic genetic diversity in a set of 77 entries and concluded that (i) European leaf beet germplasm is the most diverse, (ii) North African leaf beets likely originate from Europe, (iii) leaf beet germplasm from the Middle East and western Asia is more similar to the European sources and (iv) East Asian germplasm is different from group (i) to (iv).…”
Section: Within Species Diversity: Domesticated Formsmentioning
confidence: 99%
“…Leaf beet has never been bred intensively, thereby leading us to assume that a lot of variation is still present in leaf beet cultivars or landraces [6]. Leaf beet can be considered as a potential, valuable source of desirable characters lacking in sugar beet breeding programs [7]. With this in mind, we have decided to estimate the extent of genetic diversity within leaf beet germplasm resources.…”
Section: Introductionmentioning
confidence: 99%